Sistem Manajemen Keamanan Pangan ISO 22000 Untuk Industri Yang Berhubungan Dengan Pangan - Wawan Kurniawan (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2011)
This paper was discussing about ISO 22000. ISO 22000 is an international standard that defines the requirements of a food safety management system covering all organizations in the food chain from “farm to table”. The standard combines generally recognized key elements to ensure food safety along the food chain, including: interactive communication, system management, control of food safety hazards through pre-requisite programmes and HACCP plans, continual improvement and updating of the food safety management system. ISO 22000:2005 is also for companies seeking to integrate their quality management system, for example ISO 9001:2000 and British Retail Consortium (BRC).